\(-1 \times -1\) = \(1 \times 1\)

By cross multiplication

\(\frac{-1}{1}\) = \( \frac{1}{-1}\)

Taking square root on both sides

\(\frac{ \sqrt{-1}}{\sqrt{1}}\) = \(\frac {\sqrt{1}}{\sqrt{-1}}\)

We know that \(i\) = \(\sqrt{-1}\)

\(\frac{i}{\sqrt{1}}\) = \(\frac{\sqrt{1}}{i}\)

\(i \times i\) = \(\sqrt{1} \times \sqrt{1}\)

\(i^{2}\) = \(1\)

Also we know \(i^{2}\) = \(-1\)

This implies \(-1\) = \(1\)

Taking log on both sides we get \(log -1\) = \(log 1\)

Also \(1\) =\(-1^{2}\)

\(log -1^{3}\) = \(log -1^{2}\)

\(3 log -1\) = \( 2 log -1\)

Since \(log -1\) is not zero, we can divide by \(log -1\) on both sides we get

\(3\) = \(2\)

\(3\) = \(1\) + \(1\)

No vote yet

4 votes

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestSee Proof that -1 = 1

Log in to reply

This question was asked to me by one of my friends and I couldn't answer him and he told me that it was ajoke. But because of you I have come to know the solution. Thanks a lot.

Log in to reply

just add more problems like this...

Log in to reply

Wow .. :D Amazing

Log in to reply

hey,revan check out ur mail (revandon007@gmail.com),a surprise is waiting for u...........

Log in to reply

but can we use the idea of log of a negative no. in the proof when it is not defined....???

Log in to reply